Number Relation in The Qur’an - Fariha, Nuri Fatihatul; Shofiyya, Nada; Faradisa, Shofia Ama; Abdussakir; Masamah, Ulfa (Proceeding International Conference on Religion, Science and Education, 2022)
This article aims to find out the forms of number relations contained in the Qur'an. The method used is library research or a library approach through writings in books and journal articles. The results of this study are known that there are editors of verses in the Qur'an that contain mathematical number relations such as equal to (=), less than (<), more than (>), more than or equal to (?) and not equal to (?).